Irrigation and Drainage Sustainable Strategies and Systems - Salik Javaid, Muhammad (IntechOpen, 2015)
The sustainability of irrigation and drainage in the face of many variants and constraints like availability of water as a resource, ecological balance, socio-cultural impacts, and climate change effects lies in the strategies adopted and systems emplaced. It has always remained a challenge for the users of irrigation waters to maintain sustainability in quality and quantity. This book aims ?to explore frontiers of knowledge in coining sustainable strategies and systems direly needed in managing the quality and quantity of water required for crop irrigation, surface and root zone drainage and flood management using available tools of research and development?. Eminent authors and their colleagues possessing varied professional backgrounds and expertise have dealt with these issues concerning the strategies and systems of irrigation and drainage. This book will prove to be beneficial for crop growers, agricultural engineers, water resource managers, academicians and graduate students alike.